Stomatal proxy record of CO2 concentrations from the last termination suggests an important role for CO2 at climate change transitions - Steinthorsdottir, Margaret; Wohlfarth, Barbara; Kylander, Malin E.; Blaauw, Maarten; Reimer, Paula J. (Quaternary Science Reviews, 2013)
A new stomatal proxy-based record of CO 2 concentrations ([CO 2 ]), based on Betula nana (dwarf birch) leaves from the Hässeldala Port sedimentary sequence in south-eastern Sweden, is presented. The record is of high chronological resolution and spans most of Greenland Interstadial 1 (GI-1a to 1c, Allerød pollen zone), Greenland Stadial 1 (GS-1, Younger Dryas pollen zone) and the very beginning of the Holocene (Preboreal pollen zone). The record clearly demonstrates that i) [CO 2 ] were significantly higher than usually reported for the Last Termination and ii) the overall pattern of CO 2 evolution through the studied time period is fairly dynamic, with significant abrupt fluctuations in [CO 2 ] when the climate moved from interstadial to stadial state and vice versa. A new loss-on-ignition chemical record (used here as a proxy for temperature) lends independent support to the Hässeldala Port [CO 2 ] record. The large-amplitude fluctuations around the climate change transitions may indicate unstable climates and that " tipping-point" situations were involved in Last Termination climate evolution. The scenario presented here is in contrast to [CO 2 ] records reconstructed from air bubbles trapped in ice, which indicate lower concentrations and a gradual, linear increase of [CO 2 ] through time. The prevalent explanation for the main climate forcer during the Last Termination being ocean circulation patterns needs to re-examined, and a larger role for atmospheric [CO 2 ] considered.